Concept for Darcy-based viscosity measurement for fast-curing resin systems. (October 2021) - May, David; Mitschang, Peter
Abstract: In Resin Transfer Molding (RTM) a dry fibrous reinforcement is placed in a mold and a thermosetting resin system is then injected. Ever faster curing resins have been developed to minimize cycle times. For a thorough process design, the time- and temperature-dependent viscosity behavior needs to be known. However, the short curing times of sometimes less than 2 min often exceed the limitations of conventional measurement approaches. Necessary mixing, application and adjustment procedures lead to a "blind spot" especially at the particularly critical beginning of the reaction. This paper presents a specifically RTM-related concept for the viscosity characterization from mixing until gel point. It is based on generating a linear resin flow in a reference porous media and applying an algorithm based on Darcy's law. The overall approach and the algorithm are presented. The basic functionality is proven by using numerical simulation. Highlights: Highlights for the manuscript "Concept for Darcy-based viscosity measurement for fast-curing resin systems" Fast-curing resins systems bring conventional viscosity measurement to its limits Concept for process-oriented (Resin Transfer Molding) viscosity measurement Darcy-based processing of resin flow in porous media Numerical validation for proof-of-principle